Randomized control trial to compare the efficacy of split thickness transplant versus autologous melanocyte transplant in the management of stable vitiligo - Talukdar, Krishna; Mitra, Debdeep (International Journal of Medical Research and Review, 2016)
Background: Stable cases of vitiligo can be managed surgically and over the years there has been a shift in the management protocol from the time tested epidermal tissue grafting techniques to the newer melanocyte or cellular transplant techniques. This randomized control trial has evaluated the relative efficacy of both the transplant techniques in the management of stable cases of vitiligo with at least one year of stability. Methods: Epidermal split thickness grafts were harvested from medial aspect of thigh. In the split thickness epidermal grafting technique the donor tissue was directly transplanted on the dermabraded vitiliginous areas. In the autologous melanocyte transplant technique melanocytes were harvested from a donor split thickness graft as a melanocyte rich cell suspension, which was then transplanted to the recipient area that had been superficially dermabraded. 50 patches of vitiligo in patients were randomly allocated into 2 groups to receive either of the two interventions. Results: An excellent response was seen in 64% cases with the melanocyte cell suspension technique and in 52% with the split thickness epidermal grafting technique. Conclusion: Both the surgical techniques are effective in obtaining re-pigmentation in recalcitrant but stable lesions of vitiligo. Large areas of skin can be covered with a smaller donor skin using melanocyte transfer technique; however melanocyte transplant method is more time consuming, and a labor intensive process, requiring state of the art equipments with a sterile laboratory and dermato-surgery setup.